Policy Review: School exclusion for non-vaccinated students in Kansas - McDonald, Jennifer (My University, 2018)
Immunization plays an important role in keeping people healthy. The CDC has a recommended vaccination schedule that was developed to minimize doctor's visits and to ensure most vaccines are received prior to a child entering school. U.S. laws allow each state to develop their own policies regarding required vaccinations and school entry. Kansas law requires that all school children be immunized with vaccines designated by the Kansas Department of Health and Environment (KDHE). This statute does allow exemptions on basis of medical or religious grounds (K.S.A. 72-5209 et seq.). Local school boards and governing authorities of nonpublic schools are authorized to exclude students who have not been vaccinated according to the requirements (K.S.A. 72-5211a), but state law does not require them to do so. Each district and governing authority may create their own policies regarding exclusion at the individual level. In July of 2016, the Immunize Kansas Coalition, a group of health care providers, health department officials, researchers and educators, distributed a model school immunization policy to all school nurses in Kansas. This group works to improve vaccination rates and protect Kansans against vaccine preventable diseases. The focus of this policy was to develop a written guideline for schools to follow and to have a consistent exclusion date six week after the enrollment date.
Keywords: KDHE